PENGARUH PENERAPAN STRATEGI ELABORASI DENGAN METODE PREVIEW, QUESTION, READ, REFLECT, RECITE, AND REVIEW (PQ4R) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 PAYAKUMBUH - Anggraini, Meta; Rahmi, Rahmi; Melisa, Melisa (Pendidikan Matematika, 2013)
This research is motivated by the lack of interest of the students to read the lessons that will be studied and the students comprehention of mathematical concepts are still low , causing the outcomes of mathematics are also low. This research aims to: 1 ) Knowing how to implement student learning activities with elaboration strategies methods includes Preview, Question,Â  Read, Reflect, Recite and Review ( PQ4R ) on mathematics class VIII SMP 2 Payakumbuh. 2) Determining whether the student with an comprehention of mathematical concepts with implementation strategies elaboration of the method include Preview, Question, Read, Reflect, Recite and Review ( PQ4R ) more understand than conventional learning students in class VIII SMP 2 Payakumbuh. The type of this research is experimental research, the entire study population class VIII SMP 2 Payakumbuh. The sampling is randomly, selected VIII-D class as the experimental class and the control class is VIII-E class. Hypothesis test that used was T test. Form of the test used essay test with a reliability test is Â = 0.72 , the meaning that test has high reliability. Based on the analysis of both,Â  have average that studentâs understanding of mathematical concepts on the experimental class = 69.68, and average studentâs understanding of mathematical concepts on control = 59.06. The hypothesis , derived P â value = 0.018 < ( 0.05 ) so the hypothesis is accepted. It concluded that students understanding of mathematical concepts by applying methods PQ4R better than students comprehention of mathematical concepts with conventional learning with 95% confidence level .